Preparedness And Attributes Of Covid-19 Among Malaysian Public During The Movement Control Order - Sharifah Najwa Syed Mohamad; Sharifah Fairuz Syed Mohamad; Fathima Begum Syed Mohideen; Fatin Ahza Rosli; Nur Faraheen Abdul Rahman; Shahrina Ismail (USIM Press, 2024)
The emergence of COVID-19 has affected people worldwide from all angles, from the aspects of health, wealth, emotional and also human interactions. This study aimed to look at the attributes such as positive behaviour, awareness, preparedness and relationships among Malaysians during the implementation of movement control order (MCO), and the predictors of preparedness in facing the COVID-19 pandemic. A cross-sectional study was conducted online involving 317 respondents above the age of 18 years old. A self-administered questionnaire was developed in both Malay and English languages to assess the level of positive behaviour, awareness, preparedness and relationships, as well as their main source of information retrieval regarding COVID-19. Overall, the measured attributes in this study showed the highest level in behaviour (84.2%), followed by awareness (73.5%), preparedness (62.5%) and relationships (60.6%). Multiple regression on preparedness revealed that all variables (behaviour, awareness, and relationships) are significant (p<0.05), while gender is not. The top two sources of information the respondents refer to during the MCO are social and broadcast media. This marks the influence of social and broadcast media in an Industrial Revolution 4.0 era. Despite having good awareness and positive behaviour, the MCO may also have caused relationship issues as well as lower preparation levels in facing a deadly pandemic. It is suggested that future research to look into whether this would have any association with the mental health of Malaysians facing the pandemic. By understanding the attributes related to the MCO during the COVID-19 pandemic, it would help the government in the implementation of policies and procedures in any future pandemic.